(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
A major achievement of nephrology in the last 10-15 years was the clinical and experimental substantiation of the position that the progression of renal failure is more due to secondary hemodynamic and metabolic factors than to the activity of the primary pathological process. Unmodified and potentially modifiable risk factors for the progression of renal failure have been identified (2,7). So, dynamic observation for 6 years for 76 children who underwent nephropathy during the neonatal period. It showed that the majority of them, against the background of ongoing rehabilitation measures, later develop interstitial nephritis (IN), neurogenic bladder dysfunction or metabolic nephropathy and pyelonephritis. So, dynamic observation for 6 years for 76 children who underwent nephropathy during the neonatal period. It showed that most of them, against the background of ongoing rehabilitation measures, subsequently develop interstitial nephritis (IN), neurogenic dysfunction of the bladder or metabolic nephropathies and pyelonephritis. Among the potentially reversible risk factors for the progression of renal failure, a high value is attached to glomerular hyperfiltration and intraglomerular hypertension under the influence of angiotensin II (ANG II).